2017
DOI: 10.1080/13510002.2017.1304195
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in oxidative stress after eccentric and concentric exercise

Abstract: Objectives: Comparison of redox balance changes in the blood of women and men as a result of submaximal eccentric (ECC) and concentric (CONC) efforts. Methods: 10 women and 10 men performed three 45-minute submaximal treadmill runs at constant velocities (downhill run -ECC, uphill run -CONC and level run). Prior to the 45-minute exercises, after their completion and following 24 hours of recovery, the concentration of lactate, oxidized low-density lipoprotein (ox-LDL), 3-nitrotyrosine, uric acid (UA) and the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In our earlier research, we demonstrated that exercises at supramaximal ( Wiecek et al, 2015b , 2017a ), maximal ( Wiecek et al, 2015a , 2017b ), and submaximal intensities ( Wiecek et al, 2017c ) have influence on redox balance in the blood of women and men, and their effects are different depending on the intensity and duration of the effort as well as the type of engaged muscle work.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier research, we demonstrated that exercises at supramaximal ( Wiecek et al, 2015b , 2017a ), maximal ( Wiecek et al, 2015a , 2017b ), and submaximal intensities ( Wiecek et al, 2017c ) have influence on redox balance in the blood of women and men, and their effects are different depending on the intensity and duration of the effort as well as the type of engaged muscle work.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fact that no differences were found between sexes in muscle damage explains the absence of differences also found in oxidative stress. In contrast, in a recent study, it was shown that eccentric exercise caused impaired redox balance only in women [27].…”
Section: Discussionmentioning
confidence: 82%
“…However, ageand/or disease-induced alterations in sex hormones are major contributors to muscle wasting, and hence males and females may respond differently to DDx due to their unique hormonal profiles. Moreover, sex differences in the level of skeletal muscle oxidative stress, such as those recently reported to occur after eccentric exercise indicate women respond with accentuated impaired redox balance compared with men (Wiecek et al, 2017). Thus, it is possible, and more than likely, that differences in the level or the type of post-translational modification may be different between skeletal muscle in males and in females, which may contribute to sexdifferences in susceptibility to DDx exposure.…”
Section: Discussionmentioning
confidence: 99%